(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article covers modern approaches to strategic management in manufacturing enterprises, including digital transformation, innovation, and sustainable development, as well as their interrelationship. The article examines theoretical foundations, literature review, practical cases, and future trends. This work presents innovative methodologies aimed at ensuring the competitive advantage of enterprises and their sustainable growth in a rapidly changing global environment.